Application of Cement Clinker as Ni-Catalyst Support for Glycerol Dry Reforming - Hua Chyn Lee; Kah Weng Siew; Jolius Gimbun; Chin Kui Cheng (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
The increase in biodiesel production inevitably yield plethora of glycerol. Therefore, glycerol has been touted as the most promising source for bio-syngas (mixture of H2 and CO) production. Significantly, coking on nickel-based catalysts has been identified as a major deactivation factor in reforming technology. Indeed, coke-resistant catalyst development is essential to enhance syngas production. The current work develops cement clinker (comprised of 62.0% calcium oxide)-supported nickel catalyst (with metal loadings of 5, 10, 15 and 20 wt%) for glycerol dry reforming (CO2). Physicochemical characterization of the catalysts was performed using XRD, XRF, BET, TGA and FESEM-EDS techniques. Subsequently, reaction studies were conducted in a 7-mm ID fixed-bed stainless steel reactor at 1023 K with various CO2 partial pressures at constant weight-hourly space velocity (WHSV) of 7.2×104 ml gcat-1 h-1. Gas compositions were determined using Agilent 3000 micro-gas chromatography (GC) and Lancom III gas analyzer. Results obtained showed an increment of BET surface area up to 32-fold with Ni loading which was corroborated by FESEM images. Syngas (H2 and CO) ratios of less than 2 were being produced at 1023 K. A closer scrutiny to the transient profile revealed that the presence of CO2 higher or lower than CGR 1:1 promotes the Boudouard reaction. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)